S20 18f-fluorodeoxyglucose (18fdg) Pet Pulmonary Imaging: Comparative Methodology In Copd Patients. (10th November 2014) - Choudhury, G; Fletcher, A; Connell, M; Whitcher, B; Fergusson, S; Clark, T; Vennart, B; Kilty, I; VanBeek, E; MacNee, W
Abstract : Introduction: 18 FDG PET/CT imaging may be a useful tool to study COPD and lung inflammation; however the optimal protocol for this imaging biomarker has yet to be established. Method: We aimed to develop a combined 18 FDG-PET/CT imaging protocol optimised to quantify lung inflammation. Six patients with moderate-to-severe COPD underwent dynamic 18 FDG-PET imaging combined with blood sampling (both arterial and venous over 60 min) to determine the localised plasma activity time curve. High resolution CT (HRCT) was utilised to segmentate the lung and determine areas of emphysema. 3 sets of comparative input functions were analysed (arterial, venous and image derived arterial input functions). 18 FDG kinetics was fitted using the Patlak method. Results: Similar results were obtained using time activity curves from all three input functions. The arterial input was always found to be slightly higher than the others (Figure 1 ). Patlak analysis of the time-activity curves for each of the CT derived lung lobes allowed generation of images of slope (influx constant Ki) and intercept (initial volume of distribution) (Figure 1 ). The acquisition of HRCT co-registered to FDG-PET allows more accurate demarcation and quantification of FDG in emphysematous areas of the lung. Attempt to improve the signal by excluding voxels without COPD tissue (-935 to -300 HU) has been undertaken as well. The reproducibility of this technique is currently being studied where 20 patients are being scanned twice 4 weeks apart and compared to a baseline scan from 5 healthy controls. Conclusion: 18 FDG PET/CT imaging has the potential to be a non-invasive biomarker of lung inflammation in COPD.